Digitalisation in rural areas: Exploring perspectives and main challenges ahead - Sabrina Arcuri; Gianluca Brunori; Silvia Rolandi (Italian Review of Agricultural Economics (REA), 2023)
This paper offers a comprehensive critical review on digitalisation in rural areas, drawing on international and EU policies, scientific and grey literature and real-life examples from two European H2020 research projects. In doing so, it aims at providing a basic conceptual framework encompassing three main intervention areas, with relative sub-themes, identified as relevant for rural areas, namely: the rural digital divide, the attractiveness of rural areas and opportunities for strengthening local governance. For each of these broad themes, the role of digital tools is explored and supported by case study examples providing valuable insights and real-life applications in rural settings.
Keywords: Q0; R00; 330; digital divide; digitalisation; governance; rural areas; rural policy